Chomsky ideas and ideals - Smith, Neilson V. 1939- (Cambridge Univ. Press, 1999)
Chomsky has had a major influence on modern linguistics, psychology and philosophy. In this account of his work, Chomsky's key contributions to the study of language and the mind are analysed.
Keywords: Chomsky, Noam; Chomsky, Noam -- 1928-; Linguistique; Taalwetenschap; Linguistik; Linguistics